The Perception of Indonesian Millenial on Da’i: Knowledge, Presentation and Performance - Muhammad Choirin; Hadiyan Hadiyan; Anisa Maulita Suryana (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2023)
As a generation which has a unique character, the millennial generation is often percieved as a generation that is fashionable, world-accessible, and priotitizes simplicity. This study examines the perception of the millennial generation on the performance of da’i, specifically regarding knowledge capacity, presentation methods, and appearance. In addition, this study also aims to measure their perception of global influence on religious life. The current study uses both qualitative and quantitative approaches to get the best result. The qualitative approach consists of literature review of previous research and in-depth interviews with experts and practitioners. While the quantitative approach is to use a single regression between the variables. The findings of this study state that demography, religiosity and knowledge have a significant influence on the preacher’s performance.